The Consistory and Social Discipline in Calvin's Geneva. - Watt, Jeffrey R. (Changing Perspectives on Early Modern Europe Series, 2020)
Examines the most successful institution of social discipline in Reformation Europe: the Consistory of Geneva during the time of John Calvin.